2013
DOI: 10.3109/14767058.2013.773309
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disease and gestational diabetes mellitus (GDM): is there a connection?

Abstract: If larger studies confirm the trends observed in our study, consideration should be given to including women with known thyroid disease in the subset of women who should be offered screening for diabetes early in pregnancy and appropriate clinical surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…Of these, most were excluded after the first screening based on abstract and/or title, and 17 citations were retained. Six studies [18][19][20][21][22][23] were excluded after fulltext review of the 17 articles. Finally, 11 cohort studies [24][25][26][27][28][29][30][31][32][33][34] including 56 055 pregnant women, of whom 3903 had SCH, were included in the analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, most were excluded after the first screening based on abstract and/or title, and 17 citations were retained. Six studies [18][19][20][21][22][23] were excluded after fulltext review of the 17 articles. Finally, 11 cohort studies [24][25][26][27][28][29][30][31][32][33][34] including 56 055 pregnant women, of whom 3903 had SCH, were included in the analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Different diagnosis criteria of GDM have been used in different studies examining the relationship between SCH and GDM, and this may also lead to the inconsistent results. Currently, there is lack of unified diagnostic criteria for GDM and separate studies adopted the test methods and the cut-offs according their own national guidelines [17][18][19][20] . In our study, we used the IADPSG diagnosis criteria that is accepted by many countries [17,21,22] .…”
Section: " Discussionmentioning
confidence: 99%
“…2 A higher association of Caesarean deliveries was found between hypothyroid women with concurrent gestational diabetes by Tirosh et al as well as by Stohl et al 12,13 However, in the Turkish study by Kumru et al, no association was found between thyroid dysfunction and Caesarean section rates. 7 In this study, though the Caesarean rates were not significantly higher in the study group compared to the control, but there was a statistically significant number of Caesarean sections being done for the indication of foetal distress (p=0.00002) with 18.7% deliveries complicated by meconium stained liquor.…”
Section: Discussionmentioning
confidence: 51%